The impact of fillers on the biodegradation of plasticized PVC-materials exposed to soil microorganisms - Perushkina Elena; Sadykova Dilyara; Gotlib Elena; Sokolova Alla (E3S Web of Conferences, 2023)
Due to the growing use of polymer materials, in particular in construction sphere, the issue of their recycling at the end of their service life is particularly relevant. Being the base for flooring, plasticized PVC-compositions, are utilized by soil microbial flora, as the plasticizer EDOS has a positive effect on the microbiocenosis of the soil. It was shown that for aqueous extracts of samples of PVC-compositions, there is no toxicity for two test objects - infusoria Paramecium caudatum and crustacean Daphnia magna. Filling plasticized PVC-materials with natural wollastonite Miwoll 10-97 inhibits the processes of soil respiration, and rice husk ash and synthetic wollastonite on its base, contribute to its preservation. At the same time, the use of these fillers reduces the degree of utilization of plasticized PVC-compositions by soil microbial flora, since the plasticizer EDOS is adsorbed on their surface and becomes less accessible for soil microorganisms. This was proved by infrared spectroscopy and occurs due to the formation of hydrogen bonds between EDOS and rice husk ash.